The Effect of Principal's Leadership on the Performance of Elementary School Teachers in Tiworo Islands District - La Ubi Ubi (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aimed to analyze the influence of the principal's leadership on the performance of elementary school teachers in the Tiworo Islands sub-district. The sample in this study was 67 respondents. This study uses a quantitative approach. Principal leadership and teacher performance data were obtained using a questionnaire. The results of the inferential analysis concluded that the value of sig. = 0.000 < = 0.05, meaning that the principal's leadership has a positive effect on the performance of elementary school teachers in the Tiworo Islands sub-district